Students’ Attitude towards Translingual Practices in a Public Junior High School EFL Class in Brebes District - Savitri, Ayu Ida; Halimi, Sisilia Setiawati; Kartikaningsih, Harni (E-Structural (English Studies on Translation, Culture, Literature, and Linguistics), 2025)
Teaching EFL to public junior high school students in a district where the local people speak a regional language with a dialect different from the regional language taught at school is challenging for teachers who apply translingual practice. This study aims to reveal the students' attitudes toward their translingual practice and their teacher’s translingual practice in EFL learning. This qualitative study involved 30 students in Grade 7 of a public junior high school in Brebes District. The data were collected by using questionnaires and interviews. The result shows that the students express a positive attitude towards the teacher’s and their peers’ use of the national language since it is considered polite and proper to be used as the school subject’s delivery language. However, the students show a negative attitude towards the teacher’s use of the regional language with the local dialect as it is considered impolite or improper to be used in a class, and they show a negative attitude towards their peer’s use of full English during the lesson because they felt that they had not mastered English yet.  The teacher should carefully select the languages involved in a translingual practice to build the students’ positive attitudes. How they used their preferred languages during English lessons should be further observed to see how it helped them to learn EFL.